Penanaman Nilai-Nilai Pendidikan Karakter Melalui Mata Pelajaran Tematik - Dias Tri Arini Dias Tri Arini; Muhamad Arif (STAI Attanwir Bojonegoro, 2021)
Abstract: Currently, character education is an important point in the learning process in schools, in order to produce superior output, both in terms of spiritual, social, intellectual, and skills. Character education can be applied through activities at school, such as extracurricular activities or even during the learning process, one of which is through thematic subjects. Starting from this, the researcher wants to conduct a research with a focus on the problem: a) how is the teacher's strategy in instilling character education values ​​through thematic subjects? b) what are the obstacles faced by teachers in instilling the values ​​of character education through thematic subjects? This type of research is qualitative research, combined with a case study approach. Data collection techniques used by researchers are observation, interviews, and documentation. Meanwhile, to analyze the data, analysis techniques from Miles and Huberman were used. The data validity test used triangulation and negative case analysis. The results of this research explain that the teacher's strategy in instilling the values ​​of character education through thematic subjects at Madrasah Ibtidaiyah Raden Rahmat Sambikerep Surabaya are: coming to school on time or doing morning apples, carrying out congregational prayers, creating activities that students can do independently / without any help from others, making activities or making a work, doing activities. Meanwhile, the obstacles faced by teachers in instilling character education values ​​through thematic subjects at Madrasah Ibtidaiyah Raden Rahmat Sambikerep Surabaya are that there are still students who come late, there are some students who have not been able to do something independently, in some classes there are still students who lack of confidence when doing activities, and there are still students who differentiate between friends.